The Effect of Earning, Change in Account Payable, and Change in Account Receivable on Predicting Future Operating Cash Flows (Case Study on Food and Beverage Companies Listed in Indonesia Stock Exchange) - Muhammad Abdul Muis; Elis Puji Utami (Journal of Accounting and Finance Management, 2021)
The purpose of this study is to the analyze of how far the Ichimoku Kinko Hyo indicator can be used in technical analysis in order to predict the movement of stock prices in the future, to know the accuracy of the indicator in order to make investment decisions in capital markets and to know the risk and return result from the Ichimoku Kinko Hyo indicator after Corporate Action Policy in PT. Smartfren Telecom Tbk stock in 2019. The research methodology of this research is qualitative descriptive method with data source from the Indonesia Stock Exchange. The sampling technique of this research was purposive sampling method with monthly data and the study period is after Corporate Action Policy which is from December 2018 until November 2019. The results of this study show that the stock price movement in FREN stock using Ichimoku Kinko Hyo indicator after Corporate Action Policy in (December 2018 - February 2019), there are 3 (three) signals to buy and 3 (three) signals to sell while in (March - May 2019), there are 3 (three) signals to buy and 2 (two) signals to sell. In (June - August 2019), there are 1 (one) signal to buy and 2 (two) signals to sell. And in (September - November 2019), there are 2 (two) signals to buy and 2 (two) signals to sell. For this level of accuracy generated by using Ichimoku Kinko Hyo indicator accuracy rate equal to 60% (sixty percent) after the Corporate Action Policy in December 2018 until November 2019. While the level of risk and return generated by using Ichimoku Kinko Hyo indicator after Corporate Action Policy gave return of 187.49% (one hundred and eighty seven comma forty nine percent) and the risk of -36.43%.